Implementation of A Problem-Based Learning Model with the Help of Interactive Presentation Media from Quizziz in Increasing Student Learning Motivation in Class XI MIPA 4 in Chemistry Learning at Kebakkramat State Senior High School - Muhammad Habib Ash Shiddiqi; Setiyawan, Nurul Adi (Universitas Islam Indonesia, 2024)
This study aims to evaluate the increase in learning motivation in chemistry lessons using Quizziz interactive presentation media on the topic of buffer solutions, solubility, and solubility results. This class action research involved students of class XI MIPA 4 at SMA Negeri Kebakkramat. The Problem Based Learning (PBL) model is applied to involve students in solving real problems related to learning topics, encouraging investigation, critical thinking, and collaboration. Data collection was conducted through observation, interviews, and questionnaires, with data analysis using quantitative and qualitative descriptive techniques. The results showed that the application of the PBL model and Quizziz media succeeded in increasing student learning motivation with a success rate of 83% in cycle II. Indicators of learning motivation such as perseverance, persistence, preference for independent work, courage to find solutions, and ability to defend opinions, increased from cycle I (81.34%) to cycle II (83%). Evaluation of student motivation criteria also showed significant improvement from cycle I (47% excellent, 47% good, 6% fair) to cycle II (55% excellent, 42% good, 3% fair).